Learning management of Bachelor of Nursing program at Open University Malaysia (OUM) - Mohd Kidin Sahran; Mukherjee, T. K. (2007)
This paper describes first the OUM's BNS programme, and then presents the learning management of this BNS programme, an initial review of the students' performance in the first semester and to look at the prospects and challenges of this programme in future.